Contemporary technologies and the morality of warfare : the war of the machines - Caron, Jean-François, 1980- (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"Supported by genuine historical cases, this book argues that certain new technologies in warfare can not only be justified within the current framework of the just war theory, but that their use is mandatory from a moral perspective."--
The Nature of Current Military Technological Innovations -- Technologies and the Military's Duty of Care -- The Use of Military Technologies as a Way to Increase the Morality of Warfare -- Military Technologies, Respect for the Rules of Warfare, and Legal Accountability -- The Morality of Killing -- Technologies and the Enhanced Risk of Warfare.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on January 15, 2020).
eBooks on EBSCOhost
Keywords: Military history, Modern -- 21st century -- Case studies; Military art and science -- Technological innovations; Military art and science -- Technological innovations -- Moral and ethical aspects; Histoire militaire -- 21e siècle -- Études de cas; Art et science militaires -- Innovations; Art et science militaires -- Innovations -- Aspect moral; Military art and science -- Technological innovations; Military history, Modern; 2000-2099; Case studies